Efficacy and safety of the Chinese herbal medicine Xiao Yao San for treating anxiety: a systematic review with meta-analysis and trial sequential analysis - Wang, Yifan; Chen, Xiaofeng; Wei, Wei; Ding, Yiyun; Guo, Rongjuan; Xing, Jia; Wang, Jialin (Frontiers in Pharmacology, 2023)
Introduction: The effectiveness and safety of the Chinese herbal medicine (CHM) Xiao Yao San (XYS) used for treating anxiety disorders are still unknown. Thus, we conducted this systematic review with meta-analysis and trial sequential analysis (TSA) to determine its safety and efficacy. Methods: We searched 12 databases for relevant studies from the inception of each database till 10 August 2023. We selected randomized controlled trials to compare the efficacy and safety of XYS (including XYS only and XYS + anxiolytics) to those of anxiolytics in patients with anxiety. Results: We found 14 trials with 1,256 patients in total that met the requirements for inclusion. We assessed the majority of studies (8 out of 14) as being at high risk of bias; 6 were assessed as having a moderate risk of bias. Three trials compared oral XYS to anxiolytic medication, and 11 trials compared oral XYS plus anxiolytics to anxiolytic treatment alone. The pooled results showed that the efficacy of treatment in the XYS + anxiolytics groups was significantly higher than that of the anxiolytics alone group (RR = 1.19; 95% CI: [1.13, 1.26]; p < 0.00001; I2 = 0) and the adverse event rates in the XYS + anxiolytics groups were significantly lower than those in the anxiolytics alone group (RR = 0.44; 95% CI: [0.28, 0.82]; p = 0.001 < 0.05; I2 = 13). The efficacy of treatment in the XYS alone groups was also significantly higher than that of the anxiolytics alone groups (RR = 5.41; 95% CI: [2.23, 13.11]; p < 0.0001; I2 = 0). However, there was no statistical difference between the adverse events of the XYS alone group and the anxiolytics alone group, although the incidence of adverse events in the XYS alone group was lower than that in the anxiolytics alone group. The results of the TSA confirmed the above findings. Conclusion: The use of XYS combined with anxiolytics for treating anxiety was found to be safe and effective. However, although XYS alone is effective in the treatment of anxiety disorder, more large-scale research is needed to investigate adverse events. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=350358, identifier CRD42022350358.